The Effect of Critical Thinking Strategy in Improving the Reading Skills which included in PIRLS Test from Educational Supervisors in Jerash and Ajloun Directorate Perspective - Bani Naiem, Raheef Mohammad Mahmud (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the effect of critical thinking strategy in improving the reading skills which included in PIRLS Test from educational supervisors in Jerash and Ajloun directorate Perspective. To achieve the objectives of the study, the researcher used the descriptive quantitative analytical approach, the sample of study consisted from (70) female and male educational supervisor, it was chosen intentionally and a questionnaire for data collection; it consisted of (20) statements. The results indicated that the impact of the critical thinking strategy in improving the reading skills which included in PIRLS Test from educational supervisors in Jerash and Ajloun directorate Perspective was high with average (4.26 out of 5) and it was Positive, and there were no statistical significant differences at (α ≤ 0.05) in the variable of sex, and directorate.
Keywords: Critical Thinking Strategy; Reading Skills; PIRLS Test; Educational Supervisor